Bernard Holtzmann. La sculpture de Thasos. Corpus des reliefs II: Reliefs à thème héroïque. Volume I: Texte, Volume II: Planches. pp. 221, 84 plates. Athens: École française d’Athènes (Études Thasiennes 25). ISBN 978-2-86958-311-5, paperback €74. - Osborne, Robin (Journal of Greek Archaeology, 2020)
This volume has all the virtues of a traditional scholarly catalogue writ large. It also has the substantial drawbacks of the same genre. First, the virtues. Many years in the making, in significant part because of the sheer difficulty of accessing the material in the museum at Thasos, this is as complete a collection of the relevant Thasian material as can be achieved. Works known only from description or sketches and works of which photographs exist, but where the stone itself has disappeared, are all included. Each work is carefully traced to its modern provenance, and the plausible relationship between that provenance and where it was set up in antiquity is discussed. Each work is carefully described, and then discussed in individual commentaries which pick out the peculiar features of each relief and consider the grounds on which one might reckon the piece votive or funerary and on which one would offer a date. All of this is done with a certain lightness of touch, indeed charm, and sometimes wit. And for each piece where this is possible there is, in the Plates volume, a photograph of high quality, reproduced at a size adequate for detailed observation.